AN AUDIT OF THE LAST 500 BOWEL CANCER SCREENING PROCEDURES WITHIN THE NORTHERN TRUST. (8th June 2013) - Somerville, J; Lynch, P; Rodgers, C; Jacob, G; McCrory, D
Abstract : Introduction: The Bowel Cancer Screening Programme (BCS) in Northern Ireland offers screening every two years to all men and women aged 60 to 71. An FOB (faecal occult blood) kit is sent to the patient's home, with FIT (faecal immunochemical testing) testing if inconclusive or unsuitable test. All patients with positive tests are then offered screening with CT colography or colonoscopy. Aims/Background: To assess the detection rate of pathology during the last 500 procedures performed on patients entering the Northern Trust BCS programme and the percentage requiring follow-up procedures or surveillance. Method: Data was collected and analysed from patient records kept by the BCS Special Screening Practitioners in Whiteabbey Hospital. Results: Data was collected from the 11th January 2012 to 20th February 2013 inclusive. Of the last 500 screening procedures, 396 were colonoscopies (caecal intubation rate 93.4%), 68 CT colographies and 36 flexible sigmoidoscopies. 8% (40 patients) had a cancer detected and 48.6% (243 patients) had polyps excised. Bleeding was recorded as a complication following polypectomy in 2% (10 patients). Poor preparation complicated 5.8% (29 procedures). 22 prcoedures were abandoned–19 a decision by the colonoscopist, 3 at patient request. 91 (18.2%) patients required further investigation for screening completion - 41 required colonoscopy, 31 flexible sigmoidoscopy, 17 CT colography and 2 patients surgery for complex polyps. 131 will require a follow-up surveillance colonoscopy–38 at 1 year and 93 at 3 years. Conclusion: The BCS programme has a high pathology detection rate and many patients require further procedures to complete screening and follow-up procedures for surveillance.